MANUAL AND DIGITAL MAKE A MATCH: AN EXPERIMENTAL STUDY ON VOCABULARY AND MOTIVATION - Ni'amah, Lailin; Nur'aini, Siti; Setyaji, Arso (Universitas PGRI Semarang, 2025)
Vocabulary mastery is a crucial element of language acquisition, and students' success is significantly influenced by their motivation and the teaching methods used. Traditional approaches often struggle to keep students engaged, which has led to a growing interest in game-based learning strategies. One effective method is